Hubungan Asupan Energi dan Zat Gizi Makro dengan Tingkat Kebugaran (VO2 MAX) Atlet Pencak Silat, Sepak Takraw, dan Judo - Simanungkalit, Sintha Fransiske; Sofianita, Nur Intania; Syah, Muhammad Nur Hasan; Listiyawati, Margareta Dias; Sairah, Nurul Amrina (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
Athletes with good physical fitness will have optimal performance quality. Fitness is a crucial factor in building an athlete's performance in achieving the expected competencies. One strategy for maintaining physical fitness levels is to consume foods with balanced nutrients, especially energy and macronutrients (Carbohydrates, Protein and Fat). In this study, the relationship between energy and macronutrient intake and the fitness of Pencak Silat, Sepak Takraw and Judo athletes at DKI Jakarta Province will be examined. This research uses a quantitative observational analytical method with a cross-sectional design and is analyzed descriptively analytically to determine the desired relationship. The data normality test used the Kolmogorov-Smirnov test, resulting in normally distributed data (p>0.05). The total population in this study was 75 people, 45 men and 30 women. The results of the analysis of Recall and VO2Max data which describe each variable show that there is a significant relationship between energy and macronutrient intake and athlete fitness. Marked with a P value = 0.00 (p value < 0.05). By understanding this relationship, it is hoped that it can help design a diet program that is more effective and suits the athlete's needs based on the type of sport they are involved in, so that the athlete can achieve optimal physical fitness.